Assessment of anorexia and weight loss during the infection and recovery period of patients with coronavirus disease 2019 (COVID-19) - Masoumeh Khalighi Sikaroudi (Elsevier, 2021)
Summary: Objectives: Patients with coronavirus disease 2019 (COVID-19) can present anorexia and weight loss due to their symptoms and eating disorder which can lead to immune system weakness and increase the duration of recovery time. We aim to assess the severity and duration of anorexia and weight loss within the infection and recovery period in these patients. Method: We retrospectively identified 233 COVID-19 patients (older than 18 years) were admitted to the Rasoul-e Akram Hospital, from August to December 2020. Their medical records were reviewed by researchers. Then, patients who had inclusion criteria were asked about duration and severity of anorexia, and also weight alternation during the infection and after the recovery period. Result: Analyzed data were collected from 233 COVID-19 patients showed the mean duration of anorexia was 7.08 ± 10.41 days with a significant loss of appetite (- 75.55 ± 88.09, P-value < 0.001) at the period of anorexia compare to appetite improvement. Also, results demonstrated patients, especially males and severe illness subjects, significantly lost weight (P-value <0.001).Conclusion: anorexia and weight loss occur in people infected with the coronavirus and may affect the recovery process of these patients by reducing their food intake. The underlying mechanisms of SARS-CoV-2 related to interaction to the gastrointestinal tract and development of anorexia in these patients need to clarify in future studies.